The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1182/blood.v92.4.1350.416k24_1350_1363
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulation of T-Cell Death by CD28 Depending on Both Its Aggregation and T-Cell Receptor Triggering: A Role for Fas-FasL

Abstract: CD28 is a major coreceptor that regulates cell proliferation, anergy, and viability of T cells. The negative selection by T-cell receptor (TCR)-induced cell death of immature thymocytes as well as of activated human antigen-specific T-cell clone, requires a costimulatory signal that can be provided by CD28. Conversely, CD28-mediated signals increase expression of Bcl-XL, a survival gene, and promote survival of naive T cells cultured in the absence of antigen or costimulation. Because CD28 appears to both prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In this regard, T-cell hybridomas have served as a model for the study of AICD 33,34 ; in particular, the hybridoma DC27.10 has been previously studied for the role of costimulation in the induction of apoptosis. 37 In this report, we demonstrate that CTLA-4 can block AICD in transfectants of the murine hybridoma DC27.10 via inhibition of Fas ligand (FasL) surface expression. These findings support a model in which CTLA-4 interferes with an early TCR-signaling event linked to both IL-2 production and FasL expression.…”
Section: Introductionmentioning
confidence: 75%
“…In this regard, T-cell hybridomas have served as a model for the study of AICD 33,34 ; in particular, the hybridoma DC27.10 has been previously studied for the role of costimulation in the induction of apoptosis. 37 In this report, we demonstrate that CTLA-4 can block AICD in transfectants of the murine hybridoma DC27.10 via inhibition of Fas ligand (FasL) surface expression. These findings support a model in which CTLA-4 interferes with an early TCR-signaling event linked to both IL-2 production and FasL expression.…”
Section: Introductionmentioning
confidence: 75%
“…Meanwhile, FasL is constitutively expressed in physiologically immune‐privileged sites, such as in cells of the anterior chamber of the eye, neurons, and astrocytes of the central nervous system . Regarding the signals for inducing FasL, previous studies have reported that T‐cell‐receptor (TCR)/CD3 , CD28 , CD40, stress signaling , and IFN‐γ could initiate the expression of FasL in T cells. In pathological hepatocytes, the expression of FasL was upregulated by virus or CD40.…”
Section: Discussionmentioning
confidence: 99%
“…Following activation, T cells cluster into two major groups depending on their response to activation: those who proliferate and those who die by AICD. Major determinants of postactivation T‐cell fate seem to be costimulation through CD28, binding of IL‐2 to its receptor on T cells and the state of activation and subset affiliation of the T cell [18–23]. However, the exact roles played by these factors have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact roles played by these factors have not yet been determined. Thus, CD28 costimulation normally reduces AICD, but if given alone, CD28 signalling may induce apoptosis [18, 19]. While IL‐2 has been associated with rescue from apoptosis [20], IL‐2 has also been shown to induce apoptosis in activated T cells [24, 25].…”
Section: Discussionmentioning
confidence: 99%